2015
DOI: 10.1186/s12961-015-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

How does context influence performance of community health workers in low- and middle-income countries? Evidence from the literature

Abstract: BackgroundCommunity health workers (CHWs) are increasingly recognized as an integral component of the health workforce needed to achieve public health goals in low- and middle-income countries (LMICs). Many factors intersect to influence CHW performance. A systematic review with a narrative analysis was conducted to identify contextual factors influencing performance of CHWs.MethodsWe searched six databases for quantitative, qualitative, and mixed-methods studies that included CHWs working in promotional, prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
246
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(258 citation statements)
references
References 105 publications
11
246
1
Order By: Relevance
“…292 However, the performance of interventions and programmes is greatly influenced by numerous contextual factors, an area that requires further study. 293 It is important to distinguish between community members who volunteer for a few hours a week and full-time CHWs. All CHWs need adequate training, certification, and supervision; full-time CHWs should be remunerated, have opportunities for career advancement, and be formally recognised as part of the health system.…”
Section: Panel 5: Accelerated Medically Trained Clinicians In Sub-sahmentioning
confidence: 99%
“…292 However, the performance of interventions and programmes is greatly influenced by numerous contextual factors, an area that requires further study. 293 It is important to distinguish between community members who volunteer for a few hours a week and full-time CHWs. All CHWs need adequate training, certification, and supervision; full-time CHWs should be remunerated, have opportunities for career advancement, and be formally recognised as part of the health system.…”
Section: Panel 5: Accelerated Medically Trained Clinicians In Sub-sahmentioning
confidence: 99%
“…Community health workers (CHWs), defined as members of a community with minimal formal nursing or medical training who provide basic health and medical care to their community, are increasingly recognised as an essential part of the health workforce needed to fill this gap in human resources and achieve public health goals in LMICs 7 , 8. CHWs can have many responsibilities within a community, including social support, linking to resources and health teaching 9.…”
Section: Introductionmentioning
confidence: 99%
“…It concluded that research on CHW programs often did not capture the context in which CHW interventions take place, and that future health systems research recognize and address the complexity of contextual influences on programs [63]. Bardhan argued that control rights in governance structures should be placed with local people for better health outcomes [64].…”
Section: Resultsmentioning
confidence: 99%